Pengenalan Teknologi Informasi dan Komunikasi pada Peserta Didik Sekolah Dasar di Desa Tambangan Kelekar Kecamatan Gelumbang - Ahmad Zainuri; Zainal Berlian; Kasinyo Harto; Fathima Az Zahra; Ibrahim Ibrahim; Saipul Anwar; Sherin Destianjasari; Hidayat Hidayat (Pusat Riset dan Inovasi Nasional, 2021)
The computer is one of the electronic media that is widely used to facilitate human work in managing data and storing information (data storage) in a practical and efficient manner. In today's all-digital era, computer-based information and communication technology (ICT) is needed for all people, both adults and children. Information and communication technology greatly influences various aspects of life, including education, especially for children, who really need training and an introduction to information and communication technology so that it can help them in their daily academic activities at school. The purpose of this research is to introduce ICT and learning to operate Microsoft Word in grade 5 students at SDN 24 Gelumbang. With this activity, it is hoped that students will be able to operate computers and know the parts of the Microsoft Word application and how their use can help with schoolwork and improve abilities.